2008
DOI: 10.1038/bjp.2008.24
|View full text |Cite
|
Sign up to set email alerts
|

Modelling prefrontal cortex deficits in schizophrenia: implications for treatment

Abstract: Current treatments of schizophrenia are compromised by their inability to treat all symptoms of the disease and their sideeffects. Whilst existing antipsychotic drugs are effective against positive symptoms, they have negligible efficacy against the prefrontal cortex (PFC)-associated cognitive deficits and negative symptoms. New models that reproduce core pathophysiological features of schizophrenia are more likely to have improved predictive validity in identifying new treatments. We have developed a NMDA rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

11
108
0
6

Year Published

2009
2009
2014
2014

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 141 publications
(126 citation statements)
references
References 48 publications
(48 reference statements)
11
108
0
6
Order By: Relevance
“…Indeed, sub-chronic treatment with PCP or ketamine has been reported to decrease GABAergic markers and glucose utilization in the rat prefrontal cortex (Cochran et al, 2003;Pratt et al, 2008), consistent with observed prefrontal dysfunction in patients with schizophrenia (Lewis and Gonzalez-Burgos, 2008).…”
Section: Introductionsupporting
confidence: 63%
See 1 more Smart Citation
“…Indeed, sub-chronic treatment with PCP or ketamine has been reported to decrease GABAergic markers and glucose utilization in the rat prefrontal cortex (Cochran et al, 2003;Pratt et al, 2008), consistent with observed prefrontal dysfunction in patients with schizophrenia (Lewis and Gonzalez-Burgos, 2008).…”
Section: Introductionsupporting
confidence: 63%
“…There is ample evidence that sub-chronic NMDAR antagonist treatment affects parvalbumin-containing GABAergic inhibitory interneurons in the cortex, and these interneurons may be critical to oscillatory activity central to cognitive functions (Cochran et al, 2003;Nakazawa et al, 2012;Pratt et al, 2008); similar deficiencies are observed in the brains of patients with schizophrenia (Lewis et al, 2012). In the absence of this oscillatory control, synchronous information processing in the cortex may be disrupted.…”
Section: Discussionmentioning
confidence: 99%
“…We then generated Gaussian kernel projections for the data using the same settings as for the human studies. This showed that the acute and chronic PCP rat models, which are used routinely in studies of schizophrenia (26), gave high predictive results with precisions of greater than 80% (Fig. 5).…”
Section: Comparison Of Tac Methods With Standard Statisticalmentioning
confidence: 86%
“…There are two pharmacological models of the NMDA-R (receptor) hypofunction -acute and chronic (Pratt et al, 2008). Acute receptor antagonist model relates to a short-term administration of the NMDA-R antagonist.…”
mentioning
confidence: 99%
“…Also, a significant increase of the glutaminic acid concentration in the cingular area has been noted both in patients with an early psychosis (Théberge et al, 2002), and with prodromal schizophrenia symptoms (Stone et al, 2009). Pratt et al (2008) proposed a chronic psylocybine (PCP) model, which explains a relation between the NMDA receptors hypofunction and hypofrontality. Chronic administration of the PCP to rats caused a reduction of glucose metabolism in their prefrontal cortex, and a decrease in the expression of protein marker of gamma aminobutyric acid (GABA) interneuron's' activity.…”
mentioning
confidence: 99%